As propostas de produção textual no livro didático: uma reflexão sobre as práticas efetivadas pelos professores formados pelo PROFA - Oliveira, Maria José Houly Almeida de (2008)
The textbook has been the target of innumerable raids granted for different sectors related on the Education into Brazil. A good part, these criticisms come of scholar researchers and professors. However, its necessity and importance continue to be huge in a country where a big number of followers and professors has contact at school and at home with this type of printout. This research has the purpose of analyzing the propositions of text production in Portuguese textbook language effective by teachers from grades of the basic education that have been formed by the Program of Formation of Teachers (PROFA), seeking identify what are the qualifications constructed and developed by those teachers that may be had contributed for improvement of the practices of text production. Within the accompanying of five teachers and basing our discussion on the basis advocates at Profane, we observe the affects of this course in a continued formation at instructing practice relation with the terms of production of text. We analyzed the propositions of text production in Portuguese textbook language Com Texto e Trama adopted by all the schools of Basic education of Arapiraca. We saw that the LD needs to be enhanced, because it is composed by fountain of significant information to the teacher and educative space which enables the apprenticeship. We observed that the part of the teacher remains indispensable into the transposition process among what is suggested and its effective in classroom. The quantity of proposals that take the students to use the discursive resources is insufficient to the development of complex capacities of insertion in practices of text production.